DFT and Molecular Docking Investigation of Potential Anticancer Properties of Some Flavonoids - EHIMEN ANNASTASIA ERAZUA; Babatunde Benjamin Adeleke (Chemistry Department, The University of Brawijaya, 2019)
There is a continuous need to discover and obtain more efficient drug-like molecule to suppress cancer in human being. Recently researchers are using molecular docking technique to improve the understanding of the interaction between drug and receptor, in other to obtain novel drugs for more efficient usage. Anticancer activities of some selected flavonoids were studied using quantum chemical method through Density Functional Theory (DFT) and molecular docking approach. These Flavoniods were docked against breast cancer cell line (3s7s) using Autodock tool, AutoDockVina as docking tools and Biovia Discovery Studio 2017 for post docking analysis. The binding affinity obtained was used to correlate the inhibitory activity of these flavoniods with their calculated molecular descriptors. The obtained binding energy showed that quercetin has the highest inhibition efficiency hence it has the highest ability to inhibit 3s7s than other studied compounds. It was observed that some molecular descriptor such as band gap, dipole moment, logP and EHOMO, were significant to the inhibiting ability of quercetin in the active site of the protein.